An 1H‐MRS framework predicts the onset of Alzheimer's disease symptoms in PSEN1 mutation carriers. Issue 5 (18th November 2013) - Londono, Ana C.; Castellanos, Francisco X.; Arbelaez, Andres; Ruiz, Adriana; Aguirre‐Acevedo, Daniel C.; Richardson, Alice M.; Easteal, Simon; Lidbury, Brett A.; Arcos‐Burgos, Mauricio; Lopera, Francisco
Abstract: Background: Alzheimer's disease (AD) is the most common cause of dementia; the main risk factors are age and several recently identified genes. A major challenge for AD research is the early detection of subjects at risk. The aim of this study is to develop a predictive model using proton magnetic resonance spectroscopy ( 1 H‐MRS), a noninvasive technique that evaluates brain chemistry in vivo, for monitoring the clinical outcome of carriers of a fully penetrant mutation that causes AD. Methods: We studied 75 subjects from the largest multigenerational pedigree in the world (∼5000 people) that segregates a unique form of early‐onset Alzheimer's disease (EOAD) caused by a fully penetrant mutation in the Presenilin‐1 gene ( PSEN1 p.Glu280Ala [E280 A]). Forty‐four subjects were carriers of the mutation, and 31 were noncarriers. Seventeen carriers had either mild cognitive impairment (MCI) or early‐stage AD (collectively MCI‐AD). In right and left parietal white mater and parasagittal parietal gray matter (RPPGM and LPPGM) of the posterior cingulate gyrus and precuneus, we measured levels of the brain metabolites N‐acetylaspartate (NAA), inositol (Ins), choline (Cho), and glutamate‐glutamine complex (Glx) relative to creatine (Cr) levels (NAA/Cr, Ins/Cr, Cho/Cr, and Glx/Cr, respectively) with two‐dimensional 1 H‐MRS. Using advanced recursive partition analysis and random forest analysis, we built classificatory decision trees for both mutation carrier status and the presence of MCI‐AD symptoms, fitting them to 1 H‐MRS data while controlling for age, educational level, and sex. Results: We found that (1) the combination of LPPGM Cho/Cr <0.165 and RPPGM Glx/Cr >1.54 fully excluded carriers; (2) LPPGM Cho/Cr >0.165, RPPGM Glx/Cr <1.54, and left parietal white mater NAA/Cr >1.16 identified asymptomatic carriers with sensitivity of 97.7% and specificity of 77.4%; and (3) RPPGM NAA/Cr >1.05 defined asymptomatic subjects (independent of carrier status) with sensitivity of 100% and a specificity of 96.6%. Conclusions: Brain metabolites measured by 1 H‐MRS in the posterior cingulate gyrus and precuneus are optimally sensitive and specific potential noninvasive biomarkers of subclinical emergence of AD caused by the PSEN1 p.Glu280Ala (E280 A) mutation.